The combination of oseltamivir with azithromycin does not show additional benefits over oseltamivir monotherapy in mice infected with influenza A(H1N1)pdm2009 virus. Issue 12 (25th August 2017) - Fage, Clément; Pizzorno, Andrés; Rhéaume, Chantal; Abed, Yacine; Boivin, Guy
Abstract : The combination of azithromycin, an immunomodulator, with oseltamivir was compared to oseltamivir monotherapy in a lethal BALB/c model of influenza A(H1N1)pdm09 infection. Groups of 14‐16 mice received oral oseltamivir (10 mg/kg once daily for 5 days, starting at day 2 post‐inoculation) alone or combined to azithromycin (a single 100 mg/kg dose, injected intraperitoneally at day 3 post‐inoculation). Based on survival rates, lung viral titers, and pro‐inflammatory cytokine levels, the combination therapy did not provide obvious additional clinical/virological benefits over oseltamivir monotherapy. Additional studies are still needed to better define the potential role of adjunctive immunomodulatory therapy for severe influenza infections.